Optimalisasi Prestasi Belajar Geografi Melalui Metode Kooperatif Tipe Scramble pada Siswa Sekolah Menengah Atas: Penelitian - Amin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study primarily focuses on enhancing the academic achievement in Geography among students of Class XI IPS 4 at SMA Negeri 1 Cibitung through the implementation of the Scramble cooperative learning model. The research was initiated in response to the issue of low average daily assessment scores (65), which fell below the established Minimum Completeness Criteria (Kriteria Ketuntasan Minimal or KKM) of 72. This condition was attributed to the predominance of conventional lecture methods and a decline in student concentration during afternoon sessions. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted across three progressive cycles, each encompassing the stages of planning, action, observation, and reflection. The research subjects comprised 34 students from Class XI IPS 4. Data analysis revealed a positive and consistently significant trend in learning outcomes across each cycle. In the first cycle, the average post-test score was 66. This increased to 70.52 in the second cycle and experienced a significant surge to 81.41 in the third cycle. Furthermore, the classical completeness rate at the end of Cycle III was recorded at 85.29%, effectively surpassing the predetermined success indicator of 75%. Consequently, it can be concluded that the implementation of the Scramble technique is proven effective in stimulating student motivation and conceptual understanding through creative material arrangement activities.